2014
DOI: 10.1016/j.jacc.2014.02.617
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Elevated Levels of Intestinal Microbe-Generated Metabolite Trimethylamine-N-Oxide in Patients With Heart Failure

Abstract: BACKGROUND Altered intestinal function is prevalent in patients with heart failure (HF), but its role in adverse outcomes is unclear. OBJECTIVE This study investigated the potential pathophysiologic contributions of intestinal microbiota in HF. METHODS We examined the relationship between fasting plasma trimethylamine-N-oxide (TMAO) and all-cause mortality over 5-year follow-up in 720 stable subjects with HF. RESULTS Median TMAO level was 5.0 μM, which was higher than in non-HF subjects (3.5 -μM; p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
480
5
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 566 publications
(535 citation statements)
references
References 23 publications
21
480
5
18
Order By: Relevance
“…When comparing with reported TMAO concentrations, healthy control participants showed similar median values to previous healthy cohorts [2,6]. Patients suffering from SHF reported elevated levels to other HF cohorts [2,3], but similar to those suffering from chronic kidney disease [6]. This result, although interesting, is derived from a limited patient population but demonstrates the clinical applicability of the described method.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…When comparing with reported TMAO concentrations, healthy control participants showed similar median values to previous healthy cohorts [2,6]. Patients suffering from SHF reported elevated levels to other HF cohorts [2,3], but similar to those suffering from chronic kidney disease [6]. This result, although interesting, is derived from a limited patient population but demonstrates the clinical applicability of the described method.…”
Section: Discussionsupporting
confidence: 71%
“…To our knowledge, we describe the first example of a clinical assay utilising a Synapt generation ToF-MRM assay for a compound that can provide clinical prognostic value to a variety of diseases [1][2][3]25]. The assay is linear over nearly 3 orders of magnitude, has a limit of detection of 0.05 µmol\L and has a total injection-to-injection run time of 3 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a functional relevance of an impaired and/or altered bacterial profile as a primary risk factor or early disease marker for the initial onset of heart failure seems to be conceivable as well. Of note, recent studies have shown that intestinal bacterial‐dependent generated trimethylamine‐N‐oxide (TMAO) levels in blood are a prognostic factor for long‐term mortality risk in HF patients independent of traditional risk factors and indices 43, 44. In our study we focused on HF patients mostly in an acute state of decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…9 When analysed in a subset of chronic heart failure patients, elevated levels of TMAO were independently predictive of all-cause mortality within 5 years. 10 TMAO is commonly analysed using stable isotope dilution-LC-MS/MS with multiple reaction monitoring (MRM). In MRM, the instrument is tailored to filter a selective list of ions, perform fragmentation on them and monitor all reactions in parallel.…”
mentioning
confidence: 99%